2021
DOI: 10.1021/acsami.0c23158
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Clustering of Metalate–Extractant Complexes in Liquid–Liquid Extraction

Abstract: Effective and energy efficient separation of precious and rare metals is very important for a variety of advanced technologies. Liquid-liquid extraction (LLE) is a relatively less energy intensive separation technique, widely used in separation of lanthanides, actinides, and platinum group metals (PGMs). In LLE, the distribution of an ion between an aqueous phase and an organic phase is determined by enthalpic (coordination interactions) and entropic (fluid reorganization) contributions. The molecular scale de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 106 publications
1
56
0
Order By: Relevance
“…SFG experiments were carried out using an EKSPLA laser system, described in detail elsewhere. [56][57][58][59] Briefly, an amplified Nd:YAG laser system produces 29 ps pulses with 28 mJ energy centered at 1064 nm at a repetition rate of 50 Hz. A harmonic unit and a second harmonic crystal split the 1064 nm laser into two beams of 532 nm.…”
Section: Vibrational Sum Frequency Generation Spectroscopy Experimentsmentioning
confidence: 99%
“…SFG experiments were carried out using an EKSPLA laser system, described in detail elsewhere. [56][57][58][59] Briefly, an amplified Nd:YAG laser system produces 29 ps pulses with 28 mJ energy centered at 1064 nm at a repetition rate of 50 Hz. A harmonic unit and a second harmonic crystal split the 1064 nm laser into two beams of 532 nm.…”
Section: Vibrational Sum Frequency Generation Spectroscopy Experimentsmentioning
confidence: 99%
“…We have previously demonstrated that a sub-ensemble analysis of MD simulations can identify the populations leading to a certain VSFG signal in experiments. 12,22 However, a similar analysis is beyond the limits of this Letter and will be explained in another study.…”
mentioning
confidence: 71%
“…For instance, in liquid-liquid extraction (LLE), metal ions are transferred from an aqueous phase into an organic phase with the help of the amphiphilic extractant molecules. 12 In many cases extractants are neutral or positively charged, requiring the transfer of anions with the target metal ions in order to form neutral or anionic complexes in the organic phase. [13][14][15] Interestingly, in most cases these metal-anion complexes are not stable in the aqueous phase, raising the question where and how these complexes form.…”
mentioning
confidence: 99%
“…The VSFG measurements are acquired using an EKSPLA system, which has been described previously. 14,[16][17]41 Briefly, an amplified Nd:YAG laser system produces 29 ps pulses having 28 mJ energy centered at 1064 nm with a repetition rate of 50 Hz. The harmonic unit splits the 1064 nm laser and generates two beams of 532 nm.…”
Section: Vsfg Experimentsmentioning
confidence: 99%